To Investigate the Reduction in Kerf Taper Angle & Abrasive Waterjet lagging of Hard Ductile Inconel 625 with Abrasive Water Jet Machining with using Mathematical Model - Yadav, Navneetsinh S; Chavda, Neeraj K. (International Journal of Membrane Science and Technology, 2022)
Inconel 625 were studied to reduce in kerf taper angle by reducing water jet lagging with added polymer (PAM) to reduce the softening area when cutting the material on the abrasive waterjet cutting machine and to obtain a flat surface using the above listed materials. Used a combination of water pressure, abrasive particle size, nozzle size, polymer additive & Abrasives (Silica Sand) additive by percentage mass as process parameters & to check validation by mathematical model.